Analisis Usaha, Pemasaran, Nilai Tambah dan Strategi Pengembangan Budidaya Jamur Tiram di Kota Pekanbaru - Yeni Kusumawaty (AGRINUS : Jurnal Agro Marin Nusantara, 2026)
Oyster mushroom (Pleurotus ostreatus) agribusiness is a horticultural business with good development prospects due to high market demand, simple cultivation technology, and opportunities to increase added value through product processing. This study aims to examine business conditions, financial feasibility, marketing systems, added value of processed products, challenges, and strategies for developing oyster mushroom agribusiness in Pekanbaru City. The study used a literature review method utilizing secondary data from scientific journals, proceedings, undergraduate theses, and relevant research reports. The analysis was conducted descriptively and qualitatively through the process of identification, selection, comparison, and synthesis of previous research results. The results of the study indicate that the oyster mushroom business in Pekanbaru City is financially feasible to develop, as indicated by R/C Ratio, RCR, and BCR values greater than one. Marketing is carried out through direct sales or through traders and culinary entrepreneurs, with opportunities for improvement through digital marketing. Processing oyster mushrooms into various products such as chips, nuggets, shredded meatballs, meatballs, and mushroom flour can increase added value and income of entrepreneurs. Key challenges include limited capital, production capacity, and market access. Recommended development strategies include increasing production capacity, product diversification, digitalizing marketing, strengthening partnerships, accessing financing, and strengthening business institutions to increase the competitiveness and sustainability of the oyster mushroom agribusiness in Pekanbaru City.